Identification of surfactants aggregates on graphitic surface of carbon nanotubes - Fatirah Fadil; Nor Dalila Nor Affandi; Mohd Iqbal Misnon (Journal of Experimental Nanoscience, 2019)
There are a relatively large number of studies on surfactants facilitates the dispersion of multi-walled carbon nanotubes (MWCNTs), however reports for both orientation and size aggregation of surfactants on MWCNTs are scarcely described. In this study, we demonstrate the visualization of the surfactants aggregates onto MWCNTs using atomic force microscopic (AFM) and field emission electron scanning microscopy (FESEM) to provide information on the orientation and the grains size of surfactants-MWCNTs aggregates. MWCNTs treated with surfactants of different charges, namely sodium dodecyl sulphate (SDS), the anionic, cetyltrimethyl ammonium bromide (CTAB), the cationic and polysorbate 80 (Tween-80), the non-ionic, displayed substantial pattern of surfactant-MWCNTs surface contours. Raman spectroscopy analysis has been presented in order to report the characteristic of defective MWCNTs graphitize structure upon non-covalent adsorption of respective surfactants.